Functional properties of a manganese-activated exo-polygalacturonase produced by a thermotolerant fungus Aspergillus niveus - Maller, Alexandre; da Silva, Tony Marcio; Damásio, André Ricardo de Lima; Hirata, Izaura Yoshico; Jorge, João Atílio; Terenzi, Hector Francisco; Polizeli, Maria de Lourdes Teixeira de Moraes (Folia microbiologica, 2013)
A thermotolerant fungus identified as Aspergillus niveus was isolated from decomposing materials and it has produced excellent levels of hydrolytic enzymes that degrade plant cell walls. A. niveus germinated faster at 40 °C, presenting protein levels almost twofold higher than at 25 °C. The crude extract of the A. niveus culture was purified by diethylaminoethyl (DEAE)-cellulose, followed by Biogel P-100 column. Polygalacturonase (PG) is a glycoprotein with 37.7 % carbohydrate, molecular mass of 102.6 kDa, and isoelectric point of 5.4. The optimum temperature and pH were 50 °C and 4.0-6.5, respectively. The enzyme was stable at pH 3.0 to 9.0 for 24 h. The DEAE-cellulose derivative was about sixfold more stable at 60 °C than the free enzyme. Moreover, the monoaminoethyl-N-aminoethyl-agarose derivative was tenfold more stable than the free enzyme. PG was 232 % activated by Mn(2+). The hydrolysis product of sodium polypectate corresponded at monogalacturonic acid, which classifies the enzyme as an exo-PG. The K m, V max, K cat, and K cat/K m values were 6.7 mg/ml, 230 U/mg, 393.3/s, and 58.7 mg/ml/s, respectively. The N-terminal amino acid sequence presented 80 % identity with PglB1, PglA2, and PglA3 putative exo-PG of Aspergillus fumigatus and an exo-PG Neosartorya fischeri.
Keywords: kinetika; mangan; Molecular Weight; Polygalacturonase; molekulová hmotnost; koncentrace vodíkových iontů; izoelektrický bod; aktivátory enzymů; Isoelectric Point; Enzyme Stability; stabilita enzymů; Manganese; Cluster Analysis; Enzyme Activators; Environmental Microbiology; polygalakturonasa; Hydrogen-Ion Concentration; Temperature; mikrobiologie životního prostředí; fylogeneze; Aspergillus; Kinetics; kyseliny hexuronové; sekvenční homologie aminokyselin; Hexuronic Acids; Phylogeny; shluková analýza; teplota; Sequence Homology, Amino Acid